Intermediate language in the subtitle translation of Le Grand Voyage film into Indonesian Perjalanan Agung - Hayatul Cholsy (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2022)
Intermediate language in the subtitle translation of Le Grand Voyage film into Indonesian Perjalanan AgungThis study aimed to explore the role of intermediate language in translating the dialogue subtitle of Le Grand Voyage film from French as source language into Indonesian as target language. This study used intermediate language translation theory from Amal Al Shunnaq (2019), which was a translating process from source language into target language through other foreign language. Le Grand Voyage film is a film with religious nuance with the life of maghrébin immigrants in France as the background. The film subtitle in Indonesian were translated from English subtitle which were previously translated from French dialogue. English as the intermediate language had a very important role since it determined the subtitle translation final result in the target language. In addition to economic reasons, the role of an intermediate language was to be able to simplify or make subtitle in target language more concise, therefore it could easily adjust the space and time on the screen display, refine the translation result so that the film subtitle in target language becomes more polite, such as the loss of swear words, and determines the message from source language into target language due to cultural influences and the peculiarities of the intermediate language. Bahasa antara dalam penerjemahan subtitle film Le Grand Voyage ke dalam bahasa Indonesia Perjalanan AgungPenelitian ini bertujuan untuk mengeksplorasi peran bahasa antara dalam penerjemahan subtitle dialog film Le Grand Voyage dari bahasa sumber bahasa Prancis ke dalam bahasa sasaran bahasa Indonesia. Penelitian ini menggunakan teori penerjemahan bahasa antara atau intermediate language dari Amal Al Shunnaq (2019), yaitu proses pengalihbahasaan dari bahasa sumber ke dalam bahasa sasaran melalui bahasa asing lainnya. Film Le Grand Voyage merupakan film yang bernuansa religi dengan latar belakang kehidupan kaum imigran maghrébin di Prancis. Subtitle film dalam bahasa Indonesia diterjemahkan dari subtitle bahasa Inggris yang sebelumnya merupakan hasil terjemahan dari dialog bahasa Prancis. Bahasa Inggris sebagai bahasa antara mempunyai peran yang sangat penting karena menentukan hasil akhir terjemahan subtitle dalam bahasa sasaran. Selain alasan ekonomi, bahasa antara berperan untuk dapat menyederhanakan atau membuat subtitle dalam bahasa sasaran menjadi lebih ringkas sehingga dapat dengan mudah menyesuaikan ruang dan waktu pada tampilan layar; memperhalus hasil terjemahan sehingga subtitle film pada bahasa sasaran menjadi lebih santun, misalnya hilangnya kata umpatan; serta menentukan keakuratan pesan dari bahasa sumber ke dalam bahasa sasaran karena pengaruh budaya dan kekhasan bahasa antara.